The Influence of Female Board Member, Political Connections, and Independent Commissioners on Tax Avoidance of Property and Real Estate Companies - Tonny Stephanus Eoh; Nicki Siswandi Prayoga (International Journal of Organizational Behavior and Policy, 2023)
The objective of this research was to investigate the potential impact of female board member, political connections, and independent commissioners on tax avoidance, with leverage, firm size, and firm age as control variables. The study was carried out on IDX-listed property and real estate firms during the period spanning from 2017 to 2022. The present investigation employs secondary data sourced from property and real estate firms that are indexed on the IDX covering the period from 2017 to 2022. The study utilized a sample of 41 firms operating in the property and real estate sector. The employed methodology involves the utilization of panel data regression analysis through the utilization of the STATA software. The findings of this research indicate that tax avoidance is not influenced by female board member and independent commissioners, whereas political connections have a favorable impact on tax avoidance. Furthermore, it is observed that leverage acts as a control variable and exerts a positive influence on tax avoidance. Conversely, firm size displays a negative impact on tax avoidance, while firm age does not exhibit any significant effect on tax avoidance.